Mitochondrial Pyruvate dehydrogenase E1 of Nosema bombycis: A Marker in Microsporidian evolution - Tian LI, Xiaoqun DANG, Jinshan XU, Handeng LIU, Guoqing PAN, Zeyang ZHOU (Current Zoology, 2009)
Microsporidia are a group of intracelluar eukaryotic parasites, which can infected almost all animals, including human beings. Till now, no mitochodria but mitosome, a remnant of mitochondria was discovered in this phylum. We present here the mitochondrial pyruvate dehydrogenase E1 (PDH, including PDHα and PDHβ) of the microsporidian Nosema bombycis, the pathogen of silkworm pébrine. Compared with PDH of microsporidian Encephalitozoon cuniculi and Antonospora locustae, both subunits are conserved. The phylogeny indicated that both subunits are mitochondrial. The syntenic maps revealed the subunits organization of NbPDH is distributed in different scaffolds, similar to that of EcPDH but different with AlPDH, and the relationship between phylogeny tree and organization of PDH suggest that the AlPDH subunits organization is the ancestral style of microsporidia, and through the genome evolution, the reshuffling of the chromosome of microsporidia occurred, the adjacent style of ALPDHE1 organization changed, and the two subunits separated and located to different chromosomes in E. cuniculi. For N. bombycis and N. ceranae, they locate to different scaffolds. In order to determine NbPDH subcellular localizations, we prepared the polyclonal antibodies against NbPDH prokaryotic fusion proteins, and adopted the colloidal gold immunological electron microscopy, the expression signals of NbPDH were observed in spores however, the subcellular localization were not definited. In general, through comparison of three microsporidian PDH molecular phylogeny, subunits organization in chromosomes, localization indicated that PDH is an interesting marker in microsporidia evolution [Current Zoology 55(6): 423 – 429,2009].